PENGARUH PROGRAM AKTIVITAS FISIK BERKELOMPOK TERHADAP TINGKAT KESEPIAN LANSIA YANG TINGGAL SENDIRI - Cahyanto, Heri Nur; Viana, Natalia (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: Loneliness is a significant psychosocial problem among older adults,particularly those living alone, leading to negative impacts on mental health and overall well-being. Interventions promoting social engagement are crucial. Aim: To evaluate theeffectiveness of a structured, group-based physical activity program in reducing the level ofloneliness among older adults living alone. Method: This study used a quasi-experimentaldesign with a pretest-posttest control group approach. The sample consisted of 32 older adultsliving alone, divided into an experimental group (n=16) and a control group (n=16), selectedusing purposive sampling. The experimental group participated in a weekly group physicalactivity (senam lansia) for one month. Loneliness was measured using the UCLA LonelinessScale Version 3 before and after the intervention. Data were analyzed using the Wilcoxonsigned-rank test (α = 0.05). This research was conducted in Kelurahan Semampir 5A,Surabaya. Results: The Wilcoxon test revealed a statistically significant reduction in lonelinessscores for the experimental group (p = 0.000), but no significant change was observed in thecontrol group (p = 0.083). Conclusion: The group-based physical activity program waseffective in reducing loneliness among older adults living alone.